JENIS POHON, PEMANFAATAN SERTA KEPERCAYAAN MASYARAKAT DESA PELIATAN, KECAMATAN UBUD, GIANYAR-BALI - I W. Suarna; A. A. G. R. Dalem; N. N. Wirasiti (Environmental Research Center (PPLH) of Udayana University)
A study on identification of trees species, their use as well as what the communitybelieve about them held in Peliatan Village, Ubud District, Gianyar Regency (Bali) onFebruary, 2005. The study was carried out by taking a walk along the roads or trails whichwere assessed for their potentials as tracking trails in this village while taking notes on thetree species observed. The trees then were determined their status, their use as well as whatthe community believe about them. Results of this study show that there were 148 kinds oftrees which have been identified on this village. From the use perspective, it was revealedthat these trees could give a wide range of benefits for the community of Peliatan as well asBali in general. Their use for decorations, provides shady spots, as well as uncultivated treeswere the highest in their proportion (22%). In addition, in this village they were alsoidentified 18% of trees which believed to provide a possitive or negative impacts to humans.Most of them (73%) were believed to be related to positive impacts to humans.